FAMILY SCATOPSIDAE - Amorim, Dalton De Souza (Zootaxa, 2016)
An updated catalogue of the family Scatopsidae in Colombia is presented. Seven species of six genera have being recorded for the country, but four of these species are still undescribed. The Ectaetiinae genus Ectaetia, the Psectrosciarinae genera Anapausis and Psectrosciara, and at least the Scatopsinae genera Scatopse, Efcookella, and Abrhexoza are expected to be present in the fauna of the family in Colombia.